Modeling of Quinoacridinium Derivatives as Antitumor Agents using a QSAR analysis - Hadanu, Ruslin (Indonesian Journal of Pharmacy, 2019)
A QSAR analysis has been performed on a compound series of 1-11 quinoacridinium derivatives as internal test compounds, and compounds of 12-15 quinoacridinium derivatives as external test compounds. The electronic descriptors used in this study were atomic net charge (q), dipole moment (μ), ELUMO, EHOMO, polarizability (α), and Log P. They were calculated through HyperChem for Windows 8.0 software using semi-empirical PM3 method. The antitumor activity (IC50) of quinoacridinium derivative compounds was obtained from literature. Furthermore, the model of QSAR equation was analyzed through RML method which produced the best QSAR equation model: Log IC50 = -13.010 + 15.338(qC3) - 4.31(qC4) - 155.308(qC9) + 33.626(qC11) + 26.626(qC12) + 24.631(qC14) - 0.228(μ) - 0.621(ELUMO) - 0.066(α) + 0.233(Log P). The model of QSAR equation has a correlation coefficient n = 11, (r) = 1.00, (r2) = 1.00, SE = 0, and PRESS = 0.003. Among 28 compounds of quinoacridinium derivative which were designed, only 15 compounds, namely 16, 19-20, 22-28, 30-32, 39, and 40 compounds, have been recommended to be synthesized in the laboratory.